Impact of Sex in the Efficacy of Perioperative Desensitization Procedures in Heart Transplantation: A Retrospective Cohort Study - Nguyen, Lee S.; Salem, Joe-Elie; Bories, Marie-Cécile; Coutance, Guillaume; Amour, Julien; Bougle, Adrien; Suberbielle, Caroline; Kheav, Vissal-David; Carmagnat, Maryvonnick; Rouvier, Philippe; Kirsch, Matthias; Varnous, Shaida; et al. (Frontiers in Immunology, 2021)
Background. Sensitized patients, i.e. recipients with preformed donor-specific HLA antibodies (pfDSA), are at high-risk of developing antibody-mediated rejections (AMR) and dying after heart transplantation (HTx). Perioperative desensitization procedures were associated with better outcomes, but cause of sensitization may influence their efficacy. Methods. In sensitized patients (pfDSA>1000 mean immunofluorescence (MFI) units), we assessed the effect of perioperative desensitization by comparing treated patients to a historical control cohort. Multivariable survival analyses were performed on the time to main outcome, a composite of death and biopsy-proven AMR with 5-year follow-up. Results. The study included 68 patients: 31 control and 37 treated patients. There was no difference in preoperative variables between the two groups, including cumulative pfDSA (4026 [1788;8725] vs 4560 [3162;13392] MFI units, p=0.28). Cause of sensitization was pregnancy in 24/68, 35.3%, transfusion in 61/68, 89.7% and previous HTx in 4/68, 5.9% patients. Multivariable analysis yielded significant protective association between desensitization and events (adjusted (adj.) hazard ratio (HR)=0.44 (95% confidence interval (95CI)=0.25-0.79), p=0.006) and deleterious association between cumulative pfDSA and events (per 1000-MFI increase, adj.HR=1.028 (1.002-1.053), p=0.031). There was a sex-difference in the efficacy of desensitization: in men (n=35), benefit was significant (unadj.HR=0.33 (95CI=0.14-0.78); p=0.01), but not in women (n=33)(unadj.HR=0.52 (0.23-1.17), p=0.11). In terms of number of patients to treat, in men, 2.1 patients treated prevented 1 event, while in women, 3.1 required to be treated to prevent 1 event. Conclusion. Perioperative desensitization was associated with fewer AMR and deaths after HTx, and efficacy was more pronounced in men than women.